Influence of cement-stabilized soil enhancement on the axial bearing performance of bridge shafts: Field test and numerical simulation - Chang Duan; Zhihui Wan; Feng Zhou; Lei Wang; Zhiqi Shao (Case Studies in Construction Materials)
Post-grouted shafts (PGDS) and stiffened deep cement mixed (SDCM) shafts reinforce the surrounding soils with cement to enhance the bearing capacity of shaft foundations, and their applications are becoming increasingly widespread. Field tests involving two post-grouted shafts and two stiffened deep cement mixing shafts were conducted at the bridge foundations projects, analyzing the vertical bearing performance of the shafts with cement-stabilized soil enhancement. Additionally, numerical simulations were performed to establish calculation models for single shaft and groups of drilled shafts, PGDS, and SDCM shafts, enabling a comparative analysis of their bearing capacity performance within the identical strata. The results indicate that the post-grouted shaft demonstrated significant bearing deformation capacity, as confirmed by field tests. After grouting, the ultimate bearing capacities of DS1 and DS2 improved by 124.5 % and 110.9 %, respectively. In both single and group modeling shaft foundations, the post-grouted shafts demonstrated the highest bearing deformation characteristics, followed by the identical-size stiffened deep cement mixed shaft, while the long-core SDCM shafts and the ungrouted shafts exhibited the weakest performance. Due to interaction effects among group shafts, the total bearing capacity of the group shafts is not simply the sum of the individual shafts. Specifically, the reduction factor for group shaft capacity ranges from 0.68 to 0.79 at the Baoying Large Bridge site, while at the Yangkou Canal Bridge site, it varies from 0.66 to 0.85. The findings of this study provide valuable insights for practical engineering applications.